Ajanta history and development - Spink Walter M (Boston Leiden, 2007)
Volume Five comprises, along with introductory comments, two cave by cave guides. One which, very briefly, describes the character of each cave and its patronage, is intended to be useful for the general visitor to the site. The other, very detailed
Vol V: Cave by cave
Keywords: Ajanta caves(India)-history